KOLEKSIIKAN DIDANAU MAHALONA, LANTOA DAN MASAPI, SULAWESI SELATAN [On Collection of Fish Species in Lakes Mahalona, Lantoa and Masapi, South Sulawesi] - Renny Kurnia Hadiaty; Soetikno Wirjoatmodjo; Sulistiono Sulistiono (Jurnal Iktiologi Indonesia, 2004)
Mahalona, Lantoa and Masapi Lakes are three of the five beautiful lakes in South Sulawesi, the other two lakes are Matano and Town ti which bigger than those three. During the Dutch gouvemements there were several expedition to one, two or the five lakes. Rudolf Woltereck was the first biologist which visited and collected fishes from the all of the five lakes and published it in 1933. During 1988-1989, Dr, Maurice Kottelat recollected the fishes and found one new genus and about 8 new species, also designated the neotype of one species from Lake Towuti. A collaborative team between Indonesian Institute of Sciences (LIPI), Bogor Agriculture University and Forestry Department received a grant from Asean Regional Center for Biodiversity Conservation (ARCBC) to conduct the research in the five lakes. The results of this research are being reported in a series of scientific journal. The fish biodiversity of Lake Matano already published. This paper is the result of our interesting adventure to reach the three lakes and reporting their fish biodiversity. Twelveof the 17 of Mahalona’s fishes are the endemic species, while in Lake Lantoa there was 4 of the twelve and in Lake Masapi was only one of the twelve endemic fish species.